Dynamics of the Decomposition of Gas Molecules Containing Sulfur and Nitrogen from Char-S and Char-N Structures in Combustion and Pyrolysis Reactions - Yilmaz, Mucahit; Karabulut, Ezman; Celik, Fatih Ahmet (Taylor & Francis Inc, 2025)
Combustion states of char-S (C14H16O4S) and char-N (C18H19NO3) sub function molecules in a limited number of oxygen environments and pyrolysis states at high temperatures were examined quantum mechanically. In the study, the formation of all gases, with or without carbon, were determined. All the dynamics in which the O2 molecule could be effective in the combustion mechanism and all the elements that could affect the decomposition in the pyrolysis event were determined. The dynamics of the formation and disappearance of the highly stable CO molecule and CH2O (formaldehyde) molecules were shown in detail. It has been shown that the CO molecule is a catalysis that can bond with hydrocarbon groups and decompose them into small hydrocarbon groups at high temperature. In this study, it was shown that high temperature-dependent vibration and rotational energies, CO molecule and H-atom transfers play a role in the decomposition in the pyrolysis system, and the aromatic carbon ring group is the last particle group to decompose. In addition, the formation and dissociation dynamics of sulfoxylic acid, thioformic acid, hydrogen sulfide molecules originating from the Char-S system, as well as the formation conditions of hydrogen cyanide and pyridinyl molecules originating from the Char-N system, were determined. The study also showed that since the N-atom is located in the aromatic carbon ring, it makes the emergence of the nitrous oxide molecule difficult in pyrolysis systems.
Keywords: Sulfoxylic acid; thioformic acid; hydrogen sulfide; combustion; pyrolysis; hydrogen cyanide; pyridinyl